Experimental and numerical analysis of the Lüders phenomenon in simple shear. (February 2017) - Mazière, M.; Luis, C.; Marais, A.; Forest, S.; Gaspérini, M.
Abstract: The Lüders phenomenon is investigated in a low carbon ferritic steel under simple shear loading. Tensile and shear experiments are carried out associated with digital image correlation (DIC) measurements of the local strain field. An elastoviscoplastic constitutive law is identified with special attention paid to the choice of the equivalent stress measure in the yield function. It is then used to simulate the shear experiment using finite element analyses. Several mesh types and sizes are used to illustrate some mesh sensitivity observed in the finite element results. A regularized model based on strain gradient plasticity is then proposed to ensure fully mesh insensitive simulations and properly describe the finite thickness of the Lüders band front. The additional internal length introduced in the regularized model is identified from the DIC strain measurements. Finally, the boundary conditions best–suited for an accurate description of the shear experiment are discussed.